An integrated framework of user experience-oriented smart service requirement analysis for smart product service system development. (January 2022) - Zhou, Tongtong; Chen, Zhihua; Cao, Yong; Miao, Rui; Ming, Xinguo
Abstract: The rapid deployment of digital technologies drives the conventional product service system (PSS) to shift into a new paradigm known as smart PSS. Empowered with smart capabilities, smart PSS has great potential in creating positive user experience (UX). The requirements analysis is an essential task for successful development of smart PSS with strong UX. Nevertheless, there is still a lack of research on the requirement analysis of smart PSS by incorporating smart-enabled UX perspective. Hence, this paper proposes a framework of user experience-oriented smart service requirement (UXO-SSR) analysis for smart PSS development. At first, the relevant factors (e.g., user personas and activity journey) are integrated to conceptualize the UX in smart PSS context. Second, a four-phase model is proposed for identifying UXO-SSR, which can provide an effective tool for acquiring UX requirements of smart PSS from holistic perspective. Third, a novel asymmetric trapezium cloud-based uncertain linguistic BWM approach is developed to evaluate the priority of the identified UXO-SSRs. The approach can appropriately handle the hybrid uncertainties (i.e., hesitancy, fuzziness and randomness) of linguistic evaluation information, thereby improving the accuracy of evaluation results. Finally, a case study of smart sleep service system is presented to demonstrate the feasibility and reliability of the proposed framework.